Public Library Makerspace in Iran: A Qualitative Study on Components and Advantages - Abdolrasool Khosravi; Maryam Ravanipour; Heidar Mokhtari; Maryam Heydari; Reza BasirianJahromi (International Journal of Information Science and Management, 2025)
Libraries need to be innovative and creative to prevent a recession. As a forum for idea-making, the makerspace guarantees library dynamics and user satisfaction. This study aimed to identify the necessary factors and advantages of establishing makerspace in Iran's public libraries. This qualitative study applied A semi-structured interview as a data collection tool. The questions guiding the interviews were extracted from related literature. Content analysis was used for analyzing the data from interviews with 14 purposefully-selected public library managers. Software and hardware factors were identified as the main components for implementing makerspaces in Iran's public libraries. The main advantages of implementing makerspaces in Iran's public libraries were library services, technologies, buildings and physical evidence, and librarians and users. Each of the components has its own subcategories and related items. The consideration of elements necessary for implementing library makerspaces, plus informing about the advantages of establishing such a milieu, can be lucrative to library managers and librarians in making the library a dynamic environment for its users.